Transcriptome-Wide Analysis of RNA N6-Methyladenosine Modification in Adriamycin-Resistant Acute Myeloid Leukemia Cells - Fang, Shu; Peng, Bo; Wen, Yanan; Yang, Jingjing; Wang, Hao; Wang, Ziwei; Qian, Kun; Wei, Yan; Jiao, Yifan; Gao, Chunji; Dou, Liping (Frontiers in Genetics, 2022)
Acute myeloid leukemia (AML) is one of the most aggressive hematopoietic malignancies. Patients still suffer from refractory/relapsed disease after anthracycline-based therapy, which leads to a poor prognosis. N6-Methyladenosine (m6A) is the most abundant post-transcriptional modification in eukaryotes, the imbalance of which is reported to be associated with various pathological processes, including drug resistance. However, the relationship between m6A modification and drug resistance has not been well defined in AML. In this study, we analyzed the sequencing data of HL60 and its adriamycin-resistant cell line HL60/ADR. We found a total of 40550 m6A methylated peaks, representing 15640 genes in HL60, and 38834 m6A methylated peaks, representing 15285 genes in HL60/ADR. KEGG pathway analysis showed that pathways were enriched in the FoxO signaling pathway, p53 signaling pathway, and Notch signaling pathway. MeRIP-seq results showed that the fold enrichment of global m6A level in HL60/ADR was higher than HL60, and dot blot assay results indicated that the global m6A level was elevated in HL60/ADR cells compared with HL60 cells. Further analysis revealed that the expression level of METTL3 was elevated in HL60/ADR cells compared with HL60 cells. After a combined treatment of STM2457 (an inhibitor of METTL3) and adriamycin, the proliferation of HL60/ADR was inhibited. Thus, we hypothesized that the abnormality of m6A modification played an important role in adriamycin-resistant AML.